Comparison Of The Effectiveness And Safety Of Anemia Epoetin Alfa With Epoetin Beta Inhemodialysis Routine Patients At Haji Rsu Surabaya - Burhan; Gunawan Widodo; Anita Purnamayanti; Hesti Trisnianti Burhan Burhan (Universitas Muhammadiyah Malang, 2021)
Chronic Kidney Disease (CKD) is a disorder of the structure / function of kidney> 3 months marked by pathology and renal damage marker and impairment Glomerular filtration rate (GFR). Erythropoietin is agrowth factor hematopoietic that plays a role in the formation of red blood cells 5. Research conducted by Henry et al, on the pharmacokinetics of epoetinalfa showed the results that epoetinalfa has the effectiveness of increasing Hb concentration within 2-6 weeks with a half-life of 4-5 hours. Epoetin therapy was given with indications of Hb< 10 g/dL, no absolute iron deficiency anemia Transferrin Saturation > 20%, Serum Ferritin and no severe infection. At RSU HAJI, the insurance company bears the cost of administering epoetinalfa at a dose of 3000 IU and epoetin beta at a dose of 2000 IU to anemic patients undergoing HD, with several written conditions, namely the administration of epoetinalfa/beta given twice a week ,Hb< 10 g/dL, TSAT > 20%, FS > 200 ng/L, and no severe infection. The research subjects were divided into 2 groups, namely a group of patients receiving treatment for epoetin alpha 3000 IU/2x a week and a group of patients receiving epoetin beta anemia therapy 2000 IU/2x a week, with the direction of data collection being a combination of retrospective methods. Based on the results of research that has been conducted on the comparison of the effectiveness and safety of anemia therapy with epoetinalfa and epoetin beta in routine hemodialysis patients at RSU HAJI Surabaya.